The Influence of Financial Literacy, Digital Marketing, Network Connections, and Educational Management on Entrepreneurial Readiness among Generation Z - Kamila, Putri Nawra; Fahlia, Fahlia (Al-Qalam Institue, 2025)
This study examines the influence of financial literacy, digital marketing, and network connections on entrepreneurial readiness among Generation Z. In the face of challenges such as the demographic bonus and high youth unemployment, entrepreneurial readiness is crucial for fostering economic independence. However, many young entrepreneurs, especially in rural areas, lack sufficient competency. A quantitative approach, utilizing a survey of 100 respondents, was employed, with data analyzed using Structural Equation Modeling with Partial Least SquaresSquares (SEM-PLS). The results revealed that financial literacy, digital marketing, and network connections have a positive and significant influence on entrepreneurial readiness. These variables collectively explained 71.5% of the variation in entrepreneurial readiness, with financial literacy having the most substantial impact, followed by network connections and digital marketing. The study's findings highlight the importance of a comprehensive entrepreneurship development strategy that integrates financial education, digital skills, and networking. In the education sector, the results emphasize the need for curricula that focus on financial literacy, digital marketing, and networking to equip students with the skills necessary for entrepreneurial success and to bridge the gap between education and the entrepreneurial ecosystem.